2011
DOI: 10.1097/igc.0b013e31820fa168
|View full text |Cite
|
Sign up to set email alerts
|

Loss/Down-Regulation of Tumor Suppressor in Lung Cancer 1 Expression Is Associated With Tumor Progression and Is a Biomarker of Poor Prognosis in Ovarian Carcinoma

Abstract: Decreased protein expression of the TSLC1 gene might be important in conferring a more aggressive behavior in ovarian carcinoma. Thus, TSLC1 may be used as an independent prognostic molecular marker for patients with ovarian carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 24 publications
(23 reference statements)
1
15
0
Order By: Relevance
“…TSLC1 deletions cause cell adhesion damage and disorders, leading to the growth, invasion and metastasis of tumours. Many studies have indicated that there is low or no expression of the TSLC1 protein in lung, nasopharyngeal, cervical, breast and other cancers . In the current study, we found that the intensity and rate of TSLC1 expression were lower in CA than in HC tissues.…”
Section: Discussionsupporting
confidence: 50%
“…TSLC1 deletions cause cell adhesion damage and disorders, leading to the growth, invasion and metastasis of tumours. Many studies have indicated that there is low or no expression of the TSLC1 protein in lung, nasopharyngeal, cervical, breast and other cancers . In the current study, we found that the intensity and rate of TSLC1 expression were lower in CA than in HC tissues.…”
Section: Discussionsupporting
confidence: 50%
“…Numerous studies have implicated down-regulation of Cadm1 with poor patient prognosis [10], [12][14], [29], [30]; however, to the best of our knowledge no studies have investigated the mechanism responsible. Here we demonstrate that expression of Cadm1 in two independent cell lines resulted in either specific metastasis suppression or tumor suppression accompanied by a reduction in metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…TSLC1 protein contains three domains, extracellular, transmembrane and intracellular, which may correlate with its function. TSLC1 expression is down-regulated in many human cancers, such as laryngeal squamous carcinoma [3], uterine cervix cancer [4], ovarian carcinoma [5], breast cancer [6], nasopharyngeal carcinoma [7] and neuroblastoma [8]. It has been found that the lack of TSLC1 expression is closely related to the occurrence and progression of these cancers.…”
Section: Introductionmentioning
confidence: 99%